Pengaruh Media Busy Book Berbahan Daur Ulang Terhadap Peningkatan Motorik Halus Peserta Didik di Kelas A Tk Pertiwi II Sossok - Dzafirah, Siti; Kusyairy, Umi; Hamansah, Hamansah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Busy book media made from recycled materials is a type of book that is generally made from flannel combined with other recycled materials. This research aims to determine the effect of busy book media made from recycled materials on improving fine motor skills in students in class A, Kindergarten Pertiwi II Sossok, Mataran District, Kec. Anggeraja District. Enrekang. This research is a type of quantitative experimental approach. The experimental approach aims to test hypotheses related to cause-and-effect relationships and the population in this study is 20 students aged 4-5 years and residing in Kindergarten Pertiwi II Sossok, Mataran Village, Anggeraja District, Enrekang Regency. The data collection technique in this research uses observation and documentation which involves direct and structured observation of the results. Data analysis uses quantitative descriptive. The research results obtained show that students' fine motor skills before being treated using busy book media had an average pretest score of 14.6, which is included in the low category. After being treated with busy book media, the posttest score for students' fine motor skills increased to 32.4, which is included in the high category, of course this busy book media really influences students. Therefore, teachers are advised to use busy books made from recycled materials in the learning process to create an effective and enjoyable learning atmosphere for students